Radiographic Features of Spinal Meningioma and Schwannoma: A Novel Specific Feature―Ginkgo Leaf Sign - Yu Toda; Masashi Miyazaki; Takaomi Kobayashi; Yoshiaki Egashira; Deokcheol Lee; Hideaki Hamanaka; Shigeo Ueda; Hiromu Yoshizato; Masatsugu Tsukamoto; Tomohito Yoshihara; Hirohito Hirata; Hiroaki Konishi; et al. (Spine Surgery and Related Research)
Introduction: Meningiomas and schwannomas are common intradural-extramedullary spinal tumors. Because of their different origins, they necessitate different surgical procedures, which makes preoperative diagnosis important. Methods: In this study, clinical and imaging data for 62 patients diagnosed with either meningioma or schwannoma across multiple institutions were analyzed. Results: The average age of patients was older (67.6 vs. 58.9 years), and the frequency of females was higher (72% vs. 46%) for meningioma than for schwannoma. Meningiomas were mostly found in the thoracic region (84%), whereas schwannomas were commonly located in the lumbar region (54%). For each tumor type, specific radiological findings were identified. For meningiomas, findings included the ginkgo leaf sign (GLS) (sensitivity 58%, specificity 100%), oval shape (sensitivity 84%, specificity 63%), dural tail sign (DTS) (sensitivity 75%, specificity 100%), and intertumoral calcification (sensitivity 39%, specificity 100%). Combining GLS and DTS greatly improved sensitivity to 89% (specificity 100%). For schwannomas, specific findings included a lobule shape (sensitivity 25%, specificity 95%), dumbbell shape (sensitivity 54%, specificity 100%), and cystic changes (sensitivity 54%, specificity 97%). Conclusions: GLS may be a specific radiological feature for meningiomas and can aid in diagnosis when combined with DTS. Understanding these distinct radiological characteristics is valuable for preoperative differential diagnosis of intradural-extramedullary spinal tumors.